An ANP model for risk response assessment in large scale bridge projects. Issue 1 (2nd April 2020) - Yücelgazi, Fikri; yitmen, İbrahim
ABSTRACT: Large-scale bridge projects (LSBPs) have emerged due to the gradually increasing transportation needs of the connections between isolated regions. In planning, construction or completion of today's LSBPs, responses are applied to risks arising in areas such as financial, design, environmental and managerial. The main objective of this study is to prioritise the risk responses from the contractors' point of view used in LSBPs in Europe and the Middle East by using the analytical network process (ANP). The priorities obtained separately for Europe and the Middle East were compared between each other. The results display that Europe and the Middle East include both common and different risk responses. Two case studies, one in each region, have been conducted to further support the priority values acquired in this study. The priorities and responses obtained in this study can be used as standard risk response list for the prevention or elimination of risks during the planning, construction or completion phases of projects to be implemented in the field of LSBPs in various countries. Lastly, the priorities obtained in this study could be a mirror to detect or juxtapose changes in future studies in the same field.